Migrantophoby and Right Turn in the Western Europe - V. R. Atnashev (Евразийская интеграция: экономика, право, политика, 2019)
The paper considers main peculiarities of right-extremism and its growth in some states of the European Union. Right-extremism is a threat to the European stability and integration. Failures in the integration of immigrants, the growth of xenophobia and intolerance among local and immigrant communities cause their mutual radicalization. Nevertheless, the experience of some European countries demonstrates the lack of the population's long-term support of extremist campaigns against European integration.